Marked differences in prediabetes‐ and diabetes‐associated comorbidities between men and women—Epidemiological results from a general population‐based cohort aged 6‐80 years—The LEAD (Lung, hEart, sociAl, boDy) study. (12th February 2020) - Breyer, Marie‐Kathrin; Ofenheimer, Alina; Altziebler, Julia; Hartl, Sylvia; Burghuber, Otto C.; Studnicka, Michael; Purin, Daniela; Heinzle, Christine; Drexel, Heinz; Franssen, Frits M. E; Wouters, Emiel F. M; Harreiter, Jürgen; et al.
Abstract: Background: Based on biological and behavioural diversity sex and gender may affect comorbidities associated with prediabetes and diabetes. Besides evaluating the prevalence of prediabetes and diabetes (using fasting plasma glucose and HbA1c levels), the primary aim of the study is to investigate sex and gender differences in the prevalence of comorbidities in subjects with prediabetes and diabetes and to identify possible risk factors associated with prediabetes and diabetes. Design: This observational, population‐based cohort study included 11.014 subjects aged 6‐80 years. Examinations included blood samples, ankle‐brachial index, ECG, dual‐energy X‐ray absorptiometry scan and an interviewer‐administered questionnaire. Results: Across all ages, prevalence of prediabetes was 20.2% (male 23.6%; female 17.1%), and 5.4% for diabetes (male 7.3%; female 3.7%). The prevalence of prediabetes ranged from 4.4% (6‐<10 years) up to 40.4% (70+ years) in men and from 4.8% up to 42.3% in women. Comorbidity profile was markedly different between male and female, particularly in those with prediabetes: women more often suffered from arrhythmia, noncoronary artery disease, osteoporosis, increased systemic inflammatory biomarkers and depression, while men with prediabetes more often showed angina pectoris, myocardial infarction and media sclerosis. Conclusions: The unexpected 4.6% prevalence of prediabetes in children aged 6‐10 underscores the need for population‐based studies across all ages and the onset of prevention of diabetes at a young age. Marked differences have been found in comorbidities as men with prediabetes and diabetes more often suffer from cardiovascular disease, while women more often show arrhythmia, noncoronary artery disease, increased systemic inflammatory biomarkers and depression.